A Bibliometric Analysis of Journal of Relationship Marketing (2002–2019). Issue 4 (2nd October 2022) - Maggon, Mohita
Abstract: Journal of Relationship Marketing (JRM) is a Journal of high repute. The journal invites high-quality publications that are original and peer-reviewed in relationship marketing (RM) theory and practice. JRM is an interdisciplinary and international journal. The research topics frequently appearing in the journal include the evolution of RM in the new economy and changing paradigms; theoretical and methodological issues in RM; internal communication, quality, trust, commitment, satisfaction, loyalty, and dissolution in RM; applications of RM in different domains and industries; international perspectives in RM; and RM strategies in services economy. The journal completed 20 years of publishing in 2021. The current paper analyzes the journal's impact using bibliometric analysis from 2002 to 2019 on 289 publications. Network analysis is performed using VOSviewer software. The findings are reported in citations, coauthorship and bibliographic coupling, and other network analyses.